Enhancing Coral Survival on Deployment Devices With Microrefugia - Randall, Carly J.; Giuliano, Christine; Heyward, Andrew J.; Negri, Andrew P. (Frontiers in Marine Science, 2021)
Surviving after settlement through the first year of life is a recognised bottleneck in up-scaling reef coral restoration. Incorporating spatial refugia in settlement devices has the potential to alleviate some hazards experienced by young recruits, such as predation and accidental grazing, and can increase the likelihood of survival to size-escape thresholds. Yet optimising the design of microrefugia is challenging due to the complexity of physical and biological processes that occur at fine spatial scales around a recruit. Here, we investigated the effects of microhabitat features on the survival of Acropora tenuis spat in a year-long experimental field deployment of two types of artificial settlement devices—grooved-tiles and lattice-grids—onto three replicate racks on a shallow, central mid-shelf reef of the Great Barrier Reef. Spat survival across device types averaged between 2 and 39% and about half of all devices had at least one surviving coral after a year. While the larvae settled across all micro-habitats available on the devices, there was strong post-settlement selection for corals on the lower edges, lower surfaces, and in the grooves, with 100% mortality of recruits on upper surfaces, nearly all within the first 6 months of deployment. The device type that conferred the highest average survival (39%) was a tile with wide grooves (4 mm) cut all the way through, which significantly improved survival success over flat and comparatively featureless control tiles (13%). We hypothesise that the wide grooves provided protection from accidental grazing while also minimising sediment accumulation and allowing higher levels of light and water flow to reach the recruits than featureless control devices. We conclude that incorporating design features into deployment devices such as wide slits has the potential to substantially increase post-deployment survival success of restored corals.